An Efficient Platform for Astrocyte Differentiation from Human Induced Pluripotent Stem Cells - TCW, Julia; Wang, Minghui; Pimenova, Anna A.; Bowles, Kathryn R.; Hartley, Brigham J.; Lacin, Emre; Machlovi, Saima I.; Abdelaal, Rawan; Karch, Celeste M.; Phatnani, Hemali; Slesinger, Paul A.; Zhang, Bin; et al. (Stem cell reports, 2017)
Growing evidence implicates the importance of glia, particularly astrocytes, in neurological and psychiatric diseases. Here, we describe a rapid and robust method for the differentiation of highly pure populations of replicative astrocytes from human induced pluripotent stem cells (hiPSCs), via a neural progenitor cell (NPC) intermediate. We evaluated this protocol across 42 NPC lines (derived from 30 individuals). Transcriptomic analysis demonstrated that hiPSC-astrocytes from four individuals are highly similar to primary human fetal astrocytes and characteristic of a non-reactive state. hiPSC-astrocytes respond to inflammatory stimulants, display phagocytic capacity, and enhance microglial phagocytosis. hiPSC-astrocytes also possess spontaneous calcium transient activity. Our protocol is a reproducible, straightforward (single medium), and rapid (<30 days) method to generate populations of hiPSC-astrocytes that can be used for neuron-astrocyte and microglia-astrocyte co-cultures for the study of neuropsychiatric disorders. •hiPSC-derived astrocyte populations generated from 42 NPC lines•Transcriptomic analysis shows hiPSC-astrocytes resemble primary human astrocytes•hiPSC-astrocyte transcription is consistent with a non-reactive state•hiPSC-astrocytes undergo inflammatory response and enhance microglial phagocytosis Brennand, Goate, and colleagues report a rapid and robust method for the differentiation of highly pure populations of replicative astrocytes from human induced pluripotent stem cells (hiPSCs) via a neural progenitor cell (NPC) intermediate. hiPSC-astrocytes resemble primary human fetal astrocytes, have a transcriptional signature consistent with a non-reactive state, respond to inflammatory stimulants, and enhance microglial phagocytosis.